Document Management System and Reminder using SMS Gateway. Issue 1 (April 2020) - Haryanti, Tining; Winarno,
Abstract: This research is an observational research using descriptive analysis on rural areas that have little technological exposure to support social welfare, especially for baby. The lack of good documentation in social facility services for baby, especially on immunization has cost failure in meeting local government program's standard. This has led to suboptimal health care for baby. Another impact is that repeat immunization will not be effective for the social services themselves as there are no sufficient & reliable records. The information regarding to the implementation of health care for baby has failed to reach sizeable part of the society. As a result, many people are still not yet well-informed with the service schedule or types of the immunization suitable for their baby. This research Is done in ABC village through data collection in forms of observation, interviews and documentation. With the existence of document management system and reminder using SMS as to leverage health care for baby, it is expected that government program in terms of social health care especially for baby can be implemented optimally.